Otomatik yaş-kuru birikim örnekleme cihazının tasarımı ve yaş-kuru birikimlerdeki iyon konsantrasyonunun meteorolojik şartlarla ilişkisi - Degirmi, Mahmut (My University, 2011)
Otomatik Yaş-Kuru Birikim Örnekleme Cihazının Tasarımı ve Yaş-Kuru Birikimlerdeki İyon Konsantrasyonunun Meteorolojik Şartlarla İlişkisi Otomatik yaş-kuru birikim örnekleme cihazıyla örneklenmiş olan yağmur sularının analizi ve SO4-2, NO3- and Cl- iyonlarının zamanla değişimi incelenmiştir. Otomatik yaş-kuru birikim cihazı tasarlanıp yapımı gerçekleştirilmiştir. Cihaz elektronik ve mekanik olmak üzere iki aksamdan oluşur. Mekanik kısmı yaş ve kuru birikim kapları, kapak, kapak kolu ve metal gövdeden oluşur. Elektronik kısmı yağmur algılayıcı sensör ve çeşitli elektronik devre elemanlardan oluşmaktadır. Yağmur yağdığı gibi yağmur damlasını algılayan sensör, kuru birikim kabının üzerini kapatıp yaş birikim kabının üzerinin açmaktadır. Yağmur dindiğinde ise, yaş birikim kabının üzerini kapatıp kuru birikim kabının üzerini açmaktadır. İstanbulda 10 adet kuru birikim ve 19 adet yaş birikim örneklenmiştir. Kuru birikimlerde SO42- ve NO3- arasında anlamlı bir katsayı şunu işaret etmektedir ki her iki iyon da endüstriyel ve konutsal ısınma kaynaklıdır.

Designing Automatic Dry and Wet Depositions Sampler Device and Analyse İons Consentration of the Dry and Wet Deposition with their relation in Meteorological Conditions Investigate the variation of SO4-2, NO3- and Cl- ions of chemical compositions of precipitation using the wet-dry automatic rain sampler in this study. Temporal variations of these ions were investigated. Automatic wet-dry sampler was designed and produced. The wet-dry sampler is composed of two parts; mechanic and electronic. Mechanical part includes dry and wet cups, cover, cover lever and a metallic body. The electronic part is composed of rain drop sensor, various electronic materials. As soon as the rain starts the sensor detects the rain drop and the cover over the wet deposing cup is opened. When the rain stops the cover is opened inverse direction so wet deposition cup is closed dry deposition cup is opened. We carried out wet deposition for 19 rain events and 10 dry depositions sampling in Istanbul. The Significant coefficients between SO4-2 and NO3- concentration in dry deposition indicated that these ions have the same sources which are domestic heating and industrial activities.
Keywords: Fizik